Using the Modified Frailty Index to Predict Complications in Breast Reduction: A National Surgical Quality Improvement Program Study of 14, 160 Cases. (17th March 2022) - Liu, Helen; Akhavan, Arya; Ibelli, Taylor; Alerte, Eric; Etigunta, Suhas; Kuruvilla, Annet; Katz, Abigail; Taub, Peter
Abstract: Background: Breast reduction is a generally well-tolerated procedure with high patient satisfaction and low risk of surgical site infection and other complications. Although age, obesity, and comorbidities have historically been used as surgical risk proxies, recent literature suggests "frailty" measures, such as the modified 5-item Frailty Index (mFI-5), may be a superior predictor. Objectives: The aim of this study was to investigate if mFI-5 can predict the likelihood and magnitude of 30-day complications resulting from breast reductions. Methods: A retrospective review was performed of the National Surgical Quality Improvement Program (NSQIP) database to assess patients who underwent breast reduction without other concurrent procedures, from 2013 to 2019. mFI-5 scores were calculated for each patient, and complication data were gathered. Age, BMI, number of major comorbidities, American Association of Anesthesiologists class, smoking status, diabetes, steroid use, and mFI-5 score were compared as predictors of all-cause 30-day complications, 30-day surgical site complications of any kind, length of stay, and aggregate Clavien-Dindo complication severity score. Univariate logistic, linear regressions, and multivariate logistic regression analyses were performed to evaluate predictive value. Statistical significance was set at P < 0.05. Results: A total of 14, 160 patients were analyzed. The overall complication rate was 5.6%. The mFI-5 score significantly predicted overall 30-day complications, surgical site complications, complication severity, overnight stay, and likelihood of readmission (all P < 0.0001). Conclusions: The mFI-5 is a statistically significant predictor for adverse outcomes in breast reduction surgery. The mFI-5 is a simple and reliable tool that can be efficiently used to conduct a preoperative evaluation of patients requesting breast reductions. Level of Evidence: 4: